BOLA BAKAR MENINGKATKAN KETERAMPILAN MOTORIK SISWA SEKOLAH DASAR - Febrian, Rizky; Kurniawan, Edi; Ikhsan, Muhammad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Motor skills are an important aspect of physical education because they are closely related to movement ability, participation in physical activities, and the physical development of elementary school children. The lack of variation in learning activities may cause students to be less physically active, resulting in suboptimal motor skill development. This study aimed to analyze the effect of the slag ball game on improving the motor skills of students at SDN 3 Kebon Ayu in 2025. The study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 40 students divided into a control group and an experimental group, with 20 students in each group. The experimental group received slag ball game treatment for eight weeks with a frequency of three sessions per week, while the control group participated in regular learning activities without special treatment. Motor skill measurement was conducted using the Movement Assessment Battery for Children-Second Edition (MABC-2), which includes manual dexterity, aiming and catching, and balance components. Data were analyzed using normality tests, homogeneity tests, paired sample t-test, and independent sample t-test. The results showed that the slag ball game significantly improved students’ motor skills compared to conventional learning activities. The game activities involving running, throwing, catching, hitting, and maintaining balance provided more active and structured movement experiences for elementary school students. ABSTRAK Keterampilan motorik merupakan salah satu aspek penting dalam pendidikan jasmani karena berkaitan dengan kemampuan gerak, partisipasi aktivitas fisik, serta perkembangan fisik anak sekolah dasar. Rendahnya variasi aktivitas pembelajaran dapat menyebabkan siswa kurang aktif bergerak sehingga perkembangan keterampilan motoriknya belum optimal. Penelitian ini bertujuan untuk menganalisis pengaruh permainan bola bakar terhadap peningkatan keterampilan motorik siswa SDN 3 Kebon Ayu tahun 2025. Penelitian menggunakan pendekatan kuantitatif dengan metode quasi experimental melalui desain pretest-posttest control group design. Sampel penelitian berjumlah 40 siswa yang dibagi menjadi kelompok kontrol dan kelompok eksperimen, masing-masing terdiri atas 20 siswa. Kelompok eksperimen memperoleh perlakuan berupa permainan bola bakar selama delapan minggu dengan frekuensi tiga kali per minggu, sedangkan kelompok kontrol mengikuti pembelajaran biasa tanpa perlakuan khusus. Pengukuran keterampilan motorik menggunakan instrumen Movement Assessment Battery for Children-Second Edition (MABC-2) yang meliputi aspek manual dexterity, aiming and catching, dan balance. Data dianalisis menggunakan uji normalitas, homogenitas, paired sample t-test, dan independent sample t-test. Hasil penelitian menunjukkan bahwa permainan bola bakar mampu meningkatkan keterampilan motorik siswa secara signifikan dibandingkan pembelajaran biasa. Aktivitas permainan yang melibatkan gerak berlari, melempar, menangkap, memukul, dan menjaga keseimbangan memberikan pengalaman gerak yang lebih aktif dan terstruktur bagi siswa sekolah dasar.